Shigella dysenteriae and Shigella boydii in England and Wales during 1972 and 1973 - Rowe, B. (1974)
During 1972 and 1973 the Salmonella and Shigella Reference Laboratory examined 133 strains of Shigella dysenteriae and Shigella boydii isolated from patients in England and Wales. Of those infected 89 had recently travelled abroad and a further seven had been in close contact with travellers recently returned to this country. Though these subgroups were of little numerical significance they are of considerable epidemiological interest. The increase in tourism from the British Isles to North Africa and Asia is likely to lead to an increased incidence of infections due to these organisms, both in travellers infected abroad and in their contacts within the British Isles.